Cover Feature: Synthesis of 1, 2, 5‐Oxadiazinane Derivatives by Photochemical Cycloaddition of Nitrones with Diaminomethanes (ChemPhotoChem 6/2020). Issue 6 (26th May 2020) - Itoh, Kennosuke; Takashino, Atsushi; Ohtsuka, Atsushi; Kobe, Mizuki; Sawamura, Shunsuke; Kato, Ryo; Hirayama, Shigeto; Karaki, Fumika; Mizuguchi, Takaaki; Sato, Noriko; Tokunaga, Ken; Toda, Yasunori; et al.
Abstract : The Cover Feature illustrates that benzophenone catalyzes photochemical cycloaddition of nitrones with diaminomethanes to produce 1, 2, 5‐oxadiazinane. Japanese Kong wrestler statues flash their hands towards benzophenone to initiate the photoreaction. It looks like Kamehameha, which is drawn in a Japanese comic. 1, 2, 5‐oxadiazinanes are a new family of saturated heterocycles, which are expected to be applicable in drug synthesis. More information can be found in the Communication by Kennosuke Itoh, Hitoshi Ishida, Hideaki Fujii, and co‐workers .